Mobile Web-Based Monitoring and Coaching: Feasibility in Chronic Migraine - Sorbi, Marjolijn J; Mak, Sander B; Houtveen, Jan H; Kleiboer, Annet M; van Doornen, Lorenz JP (JMIR Publications, 2007)
BackgroundThe Internet can facilitate diary monitoring (experience sampling, ecological momentary assessment) and behavioral coaching. Online digital assistance (ODA) is a generic tool for mobile Web-based use, intended as an adjuvant to face-to-face or Internet-based cognitive behavioral treatment. A current ODA application was designed to support home-based training of behavioral attack prevention in chronic migraine, focusing on the identification of attack precursors and the support of preventive health behaviour. ObjectiveThe aim was to establish feasibility of the ODA approach in terms of technical problems and participant compliance, and ODA acceptability on the basis of ratings of user-friendliness, potential burden, and perceived support of the training for behavioral attack prevention in migraine. MethodsODA combines mobile electronic diary monitoring with direct human online coaching of health behavior according to the information from the diary. The diary contains three parts covering the following: (1) migraine headache and medication use, (2) attack precursors, and (3) self-relaxation and other preventive behavior; in addition, menstruation (assessed in the evening diary) and disturbed sleep (assessed in the morning diary) is monitored. The pilot study consisted of two runs conducted with a total of five women with chronic migraine without aura. ODA was tested for 8.5 days (range 4-12 days) per participant. The first test run with three participants tested 4-5 diary prompts per day. The second run with another three participants (including one subject who participated in both runs) tested a reduced prompting scheme (2-3 prompts per day) and minor adaptations to the diary. Online coaching was executed twice daily on workdays. ResultsODA feasibility was established on the basis of acceptable data loss (1.2% due to the personal digital assistant; 5.6% due to failing Internet transmission) and good participant compliance (86.8% in the second run). Run 1 revealed some annoyance with the number of prompts per day. Overall ODA acceptability was evident by the positive participant responses concerning user-friendliness, absence of burden, and perceived support of migraine attack prevention. The software was adapted to further increase the flexibility of the application. ConclusionsODA is feasible and well accepted. Tolerability is a sensitive issue, and the balance between benefit and burden must be considered with care. ODA offers a generic tool to combine mobile coaching with diary monitoring,independently of time and space. ODA effects on improvement of migraine remain to be established.